2022
DOI: 10.1021/acsami.2c06855
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic Laser Activator for Both UV and NIR Lasers: Preparation of Circuits on Polymer Substrates by Selective Metallization

Abstract: In laser-induced selective metallization (LISM), conventional laser activators only work at a single laser wavelength. This study reported a new laser activator (MoO3) very suitable for both 355 nm UV and 1064 nm near-infrared (NIR) lasers for the first time. When applying MoO3 to polymers, the prepared Cu layer on laser-activated polymers showed a good conductivity (2.63 × 106 Ω–1·m–1) and excellent adhesion. Scanning electron microscopy, optical microscopy, and resistance analysis revealed the excellent LISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…This peak is due to the thermal oxidation on the surface at high temperatures during the laser activation . The peak of CO generated by a 1064 nm NIR laser is apparently larger than that produced by a 355 nm UV laser, indicating that the NIR laser’s thermal effect is greater than that of the UV laser, which corresponds to our previous conclusion . Since the NIR laser’s thermal effect is higher than that of the UV laser, the composites’ surface is ablated and vaporized to a greater extent at the moment of NIR laser activation, and therefore, the “pit” generated by the NIR laser is larger and the surface appears darker (Figures a,b, and S5).…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This peak is due to the thermal oxidation on the surface at high temperatures during the laser activation . The peak of CO generated by a 1064 nm NIR laser is apparently larger than that produced by a 355 nm UV laser, indicating that the NIR laser’s thermal effect is greater than that of the UV laser, which corresponds to our previous conclusion . Since the NIR laser’s thermal effect is higher than that of the UV laser, the composites’ surface is ablated and vaporized to a greater extent at the moment of NIR laser activation, and therefore, the “pit” generated by the NIR laser is larger and the surface appears darker (Figures a,b, and S5).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The characterizations revealed that the mechanism of laser activation for copper pyrophosphate was the reduction mechanism, which was entirely different from our previous study. 33 S2. Hemispherical and tileshaped 3D parts were prepared.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations